2020
DOI: 10.34172/joddd.2020.040
|View full text |Cite
|
Sign up to set email alerts
|

Root canal debridement efficacy of heated sodium hypochlorite in conjunction with passive ultrasonic agitation: An ex vivo study

Abstract: Background. This study aimed to investigate the endodontic debridement efficacy of different sodium hypochlorite (NaOCl) irrigation regimens with and without ultrasonic agitation, followed by ethylenediaminetetraacetic acid (EDTA) via scanning electron microscopy (SEM) after using a rotary instrumentation system. Methods. Mandibular premolars (n=50) were randomly divided into five experimental groups (n=10) for root canal instrumentation with ProTaper Universal rotary system up to F3. The root canal system was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Clinicians advise heated NaOCl intracanal ultrasonic activation because it achieves superior dentin tubule penetration and canal purity compared to syringe activation or ultrasonic activation alone [61]. In the side dentin tubules that remained contaminated after using either ultrasonic activation or thermal activation alone, better pulp dissolution was obtained when thermal and ultrasonic activation were combined [70].…”
Section: Activation Of Irrigantsmentioning
confidence: 99%
“…Clinicians advise heated NaOCl intracanal ultrasonic activation because it achieves superior dentin tubule penetration and canal purity compared to syringe activation or ultrasonic activation alone [61]. In the side dentin tubules that remained contaminated after using either ultrasonic activation or thermal activation alone, better pulp dissolution was obtained when thermal and ultrasonic activation were combined [70].…”
Section: Activation Of Irrigantsmentioning
confidence: 99%
“…In recent years, researchers have shown interest in increasing the efficiency of NaOCl through heating. Heating the NaOCI solution enhances its flow and reaction rate, resulting in increased antimicrobial activity and tissue dissolution effect[ 11 , 25 ]. There are two methods of heating NaOCI in the root canal: extra-oral heating, where the solution is heated outside the canal, and intracanal heating, where heat carriers are used to heat the solution after it is placed in the canal.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Damade et. [ 25 ] compared the amount of debris removal using intracanal and extra-orally heated NaOCI solutions with and without ultrasonic activation. They found that intracanal heating removed more debris and had a significant effect.…”
Section: Discussionmentioning
confidence: 99%